THE SIPIROK GODANG COMMUNITY'S RESPONSE TO GOVERNMENT REGULATION - Muhammad Faiz Muhtadi Siregar; Wahyu Wiji Utomo; Aminuddin Aminuddin (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
The study aims to measure the level of knowledge among the residents of Sipirok Godang Urban Village (Kelurahan), Sipirok District, South Tapanuli Regency, regarding this regulation and to analyze their responses to the DPR-RI as the institution that played a role in the policy process. A descriptive-correlational quantitative approach was employed, utilizing a five-point Likert scale questionnaire distributed to 51 respondents; data were analyzed using descriptive statistics and Pearson correlation. The results indicate that the community's knowledge level falls within the medium-to-high category (mean score of 3.64 on a 5-point scale; 52.9% of respondents fell into the high category), whereas the community's response to the DPR-RI's performance tended to be moderate and critical (mean score of 3.24; only 33.3% fell into the high/positive category). Correlation analysis revealed a significant positive relationship between the level of knowledge and the response to the DPR-RI (r = 0.568; p < 0.001), indicating that the more the public understands the policy's substance, the more likely they are to adopt a critical-evaluative stance rather than merely accepting it passively. Other findings reveal a cross-category consensus that the policy on state officials' financial entitlements requires review (mean score of 3.96), regardless of the respondents' level of trust in the DPR-RI. This study contributes to the understanding of public policy literacy at the local (urban village) level and underscores that increasing citizens' knowledge does not automatically boost political trust; instead, it can foster an attitude of civic oversight regarding the legislative institution.